Making it “work”: mothers’ perceptions of workplace breastfeeding and pumping at Dutch universities - Maike Hentges (BMC, 2021)
Abstract Background Dutch breastfeeding rates are below World Health Organization’s recommendations and targets despite the benefits for individuals and society. Increasing the rates is complex due to multiple breastfeeding determinants, of which maternal education and employment are dominant. This study aimed to identify the perceptions and experiences of mothers employed at Dutch universities regarding barriers and enablers to workplace breastfeeding and pumping. Methods The study adopted a descriptive, qualitative research design. Thirteen semi-structured online interviews, underpinned by the Social Ecological Model, were conducted in 2020 with three experts and ten academic employees from five universities who had breastfed or pumped at work within the past five years. Qualitative data were examined through a thematic analysis. Results Four main themes were identified: physical work environment, social support, work culture and organisation, policies and legal rights. Most mothers had more negative than positive experiences combining breastfeeding with work. They were unable to exercise their rights as a breastfeeding employee due to inappropriate and inaccessible lactation rooms, a lack of communication and information-provision, other people’s lack of awareness, inflexible working hours and unadjusted workloads, especially for teaching positions. All participants found the duration of Dutch maternity leave too short. Conclusions Universities need to increase institutional efforts at multiple levels and meet their legal obligations to support breastfeeding employees. Workplace interventions should be combined with more political commitment to normalise breastfeeding, monitor compliance with maternity protection provisions at work and prolong parental leave to encourage breastfeeding continuation.